Bridge of Rainbow: Association Between Internet-Based Social Media Use and Homosexuality Inclusion in China - Jiang, Yao; Yang, Fan (Frontiers in Psychology, 2022)
By using the nationally representative dataset of China Labor-force Dynamics Survey, this paper explored the relationship between internet-based social media use and Chinese people’s homosexuality inclusion. Addressing endogeneity by using an instrumental variable approach, the results of instrumental variable-ordered probit model indicated that individuals’ internet-based social media use had a positive and significant association with their homosexuality inclusion. Furthermore, the heterogeneity analysis revealed that the heterogeneous effects of internet-based social media use on homosexuality inclusion caused by income, gender, and region. The homosexuality inclusion of respondents with higher income, respondents of female gender, and respondents located in eastern region of China was found to be more evidently associated with internet-based social media use. The functional mechanism analysis suggested that the number of respondents’ LGBT friends mediated the overall relationship between internet-based social media use and homosexuality inclusion. The robustness check showed that the results were robust cross different models. The findings in this paper provide new evidence that the effect of information technology development on individual perception and behavior in Chinese context.